Effect of Zinc Salts on Respiratory Syncytial Virus Replication - Suara, Rahaman O. (American Society for Microbiology, 2004)
Zinc supplementation decreases the morbidity of lower respiratory tract infection in pediatric patients in the developing world. We sought to determine if zinc mediates a specific inhibitory effect against the major cause of pediatric lower respiratory tract disease, respiratory syncytial virus (RSV). We determined the in vitro inhibitory effect of three zinc salts (zinc acetate, lactate, and sulfate) on the replication of RSV at various concentrations of 10 and 1 mM and 100 and 10 μM. The degree of inhibition of RSV replication was examined in the presence of zinc during preincubation, adsorption, or penetration and was compared with that caused by salts of other divalent cations. Complete inhibition of RSV plaque formation was observed at 1 and 10 mM, representing reductions that were ≥10(6)-fold. At the lowest concentration tested, 10 μM, we observed ≥1,000-fold reductions in RSV yield when zinc was present during preincubation, adsorption, penetration, or egress of virus. The therapeutic indices, determined as ratios of 50% toxicity concentration to 50% inhibitory concentration, were 100, 150, and 120 for zinc acetate, zinc lactate, and zinc sulfate, respectively. The inhibitory effect of zinc salts on RSV was concentration dependent and was not observed with other salts containing divalent cations such as calcium, magnesium, and manganese. RSV plaque formation was prevented by pretreatment of HEp-2 cell monolayer cultures with zinc or by addition of zinc to methylcellulose overlay media after infection. The results of this study suggest that zinc mediates antiviral activity on RSV by altering the ability of the cell to support RSV replication.